Nanocellulose for Paper and Textile Coating: The Importance of Surface Chemistry. Issue 8 (23rd August 2022) - Spagnuolo, Laura; D'Orsi, Rosarita; Operamolla, Alessandra
Abstract: Nanocellulose has received enormous scientific interest for its abundance, easy manufacturing, biodegradability, and low cost. Cellulose nanocrystals (CNCs) and cellulose nanofibers (CNFs) are ideal candidates to replace plastic coating in the textile and paper industry. Thanks to their capacity to form an interconnected network kept together by hydrogen bonds, nanocelluloses perform an unprecedented strengthening action towards cellulose‐ and other fiber‐based materials. Furthermore, nanocellulose use implies greener application procedures, such as deposition from water. The surface chemistry of nanocellulose plays a pivotal role in influencing the performance of the coating: tailored surface functionalization can introduce several properties, such as gas or grease barrier, hydrophobicity, antibacterial and anti‐UV behavior. This review summarizes recent achievements in the use of nanocellulose for paper and textile coating, evidencing critical aspects of coating performances related to deposition technique, nanocellulose morphology, and surface functionalization. Furthermore, beyond focusing on the aspects strictly related to large‐scale coating applications for paper and textile industries, this review includes recent achievements in the use of nanocellulose coating for the safeguarding of Cultural Heritage, an extremely noble and interesting emerging application of nanocellulose, focusing on consolidation of historical paper and archaeological textile. Finally, nanocellulose use in electronic devices as an electrode modifier is highlighted. Abstract : The use of nanocellulose for coating paper or textiles is discussed in this Review article. Special attention is paid to the importance of surface functionalization to influence the coating properties. Furthermore, this review offers a view on applications of nanocellulose coating to electronic paper and for the consolidation of historical paper or archaeological textile artworks.